Efforts to Improve Teacher Creativity Through Online Learning Models During the Covid-19 Pandemic at SD Negeri 2 Rempe - Mukhsen (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
This study aims to determine the online learning model in increasing the creativity and initiative of teachers in managing learning at home at SD Negeri 2 Rempe. The type of research conducted is school action research (PTS) using Elliot's model. The research was held at SD Negeri 2 Rempe in the 2019/2020 school year during the Covsid 19 pandemic. The research subjects were grade 1, 2, 3, 4, and Grade 5 teachers. The object of the research was learning at home through online learning during the pandemic. covid-19. Data collection is through observation and documentation and then analyzed qualitatively. Based on the results of the study, it shows that the online learning model can overcome and be a solution in implementing learning during the COVID-19 pandemic by involving the creativity and initiative of teachers to manage to learn at home. The creativity and initiative of teachers have increased in making lesson plans by 18%, online learning management by 12%, student activity by 17%, and student learning scores by 9.6% from cycle I to cycle II in learning.